2011
DOI: 10.1098/rspb.2010.2602
|View full text |Cite
|
Sign up to set email alerts
|

Learning to count begins in infancy: evidence from 18 month olds' visual preferences

Abstract: We used a preferential looking paradigm to evaluate infants' preferences for correct versus incorrect counting. Infants viewed a video depicting six fish. In the correct counting sequence, a hand pointed to each fish in turn, accompanied by verbal counting up to six. In the incorrect counting sequence, the hand moved between two of the six fish while there was still verbal counting to six, thereby violating the one-to-one correspondence principle of correct counting. Experiment 1 showed that Australian 18 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 14 publications
(32 reference statements)
6
40
0
3
Order By: Relevance
“…Many children in Western cultures begin experiencing integer words starting in infancy, in the form of hearing parents or caregivers engage in verbal counting (Goldstein, Cole, & Cordes, ). By 18 months, infants are sensitive to some procedural aspects of counting, preferring to watch correct counting over counting that violates the principles of one‐to‐one correspondence or stable order (Ip, Imuta, & Slaughter, ; Slaughter, Itakura, Kutsuki, & Siegal, ). Yet, children apparently do not map between individual number words in the counting sequence and particular approximate numerosities until age 4 years or later.…”
Section: Introductionmentioning
confidence: 99%
“…Many children in Western cultures begin experiencing integer words starting in infancy, in the form of hearing parents or caregivers engage in verbal counting (Goldstein, Cole, & Cordes, ). By 18 months, infants are sensitive to some procedural aspects of counting, preferring to watch correct counting over counting that violates the principles of one‐to‐one correspondence or stable order (Ip, Imuta, & Slaughter, ; Slaughter, Itakura, Kutsuki, & Siegal, ). Yet, children apparently do not map between individual number words in the counting sequence and particular approximate numerosities until age 4 years or later.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the guidelines at age 48 months, children must begin learning about numbers and counting much earlier than that-and in high-SES households, at least, they do. One study showed that high-SES children in Australia and Japan begin to recognize the counting list of their language and expect it to be paired with a correct counting procedure sometime between 15 and 18 months of age (Slaughter, Itakura, Kutsuki, & Siegal, 2011).…”
Section: Spoken Numbersmentioning
confidence: 99%
“…Children start to learn these rules about counting as early as 15-18 months of age, depending on how much counting they witness (Slaughter, Itakura, Kutsuki, & Siegal, 2011). But reciting the list of counting words, even while pointing to things, is not the same as understanding how counting reveals the number of things in a set .…”
Section: Acquiring a System Of Representation For Exact Numbersmentioning
confidence: 99%
“…Certainly, children do treat 'one' as the unique first term in the sequence (e.g., Fuson, 1988). And there is evidence that even children as young as 18 months recognize the words in the counting list as separate from other kinds of words (Slaughter et al, 2011). As far as I know, no one has tested the question of whether children understand that if 'next(k)' = 'next(j)' then 'k'='j,' so that question remains open.…”
Section: Rips's Argument Against Bootstrappingmentioning
confidence: 99%